Flame-retardant PCB copper-clad substrate and preparation method thereof

By combining modified glass fiber cloth and resin glue, combined with multi-stage heating and curing technology, a flame-retardant PCB copper-clad substrate with improved flame retardant, heat resistance and reduced dielectric constant was prepared, which solved the problem of insufficient performance of copper-clad substrates in the prior art.

CN119767548AActive Publication Date: 2025-04-04SHUOCHUANG ELECTRONICS (HUAIAN) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411748193.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The flame retardancy, heat resistance and dielectric properties of copper clad substrates cannot meet the needs of the development of high-performance PCBs.

Method used

By fully impregnating the modified glass fiber cloth in a resin solution for a copper-clad substrate and performing a multi-stage heating and curing treatment, a flame-retardant PCB copper-clad substrate with improved flame retardant, heat resistance and reduced dielectric constant was prepared.

Benefits of technology

The flame retardancy and heat resistance of the PCB copper clad substrate are significantly improved, while reducing the dielectric constant to meet the development needs of high-performance PCBs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164296430000151
    Figure BDA0005164296430000151
Patent Text Reader

Abstract

The invention relates to the technical field of circuit boards, and particularly discloses a flame-retardant PCB copper-clad substrate and a preparation method thereof.The flame-retardant PCB copper-clad substrate is prepared by taking fluorine-containing pyridine benzoxazine and epoxy resin as resin matrixes, adding 4, 4-diaminodiphenyl-methane, KH-550 modified nano-silica hollow spheres and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as additives, and preparing the flame-retardant PCB copper-clad substrate. The resin glue solution for the copper-clad substrate is prepared, KH-560 modified glass fiber cloth is soaked in the resin glue solution for the copper-clad substrate and then stacked together, and the glass fiber cloth and a copper foil are subjected to hot pressing together to form the flame-retardant PCB copper-clad substrate. The flame-retardant PCB copper-clad substrate is not only good in heat resistance and flame retardance, but also low in dielectric constant and dielectric loss, and meets the requirements of high-frequency, high-speed and high-performance PCBs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of circuit boards, and in particular to a flame-retardant PCB copper-clad substrate and a preparation method thereof. Background Art

[0002] Printed circuit board (PCB) is an electronic component that reduces the wiring between electronic parts and reduces production costs by printing a conductive metal coating on an insulating substrate. It is a product of the development of electronic information technology towards small size, light weight and multi-function. As a carrier for electrical connection between electronic components, PCB has a wide range of applications, from remote controls, radios, flashlights to televisions, computers, and aircraft. At present, PCB is developing towards high precision, high density, high performance, microporous, thin and high-rise. As the main substrate material for manufacturing PCB, the quality of copper clad substrate affects the performance, quality, level and other properties of PCB. Therefore, copper clad substrate should also have better performance. However, the flame retardancy, heat resistance and dielectric properties of copper clad substrate cannot meet the development needs of high-performance PCB. Summary of the invention

[0003] The object of the present invention is to provide a flame-retardant PCB copper-clad substrate and a preparation method thereof, so as to solve the problems that the copper-clad substrate has insufficient flame retardancy, insufficient heat resistance and insufficient dielectric properties.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A method for preparing a flame-retardant PCB copper-clad substrate, the preparation method comprising:

[0006] After cutting the glass fiber cloth into a suitable size, modifying it with KH-560, fully immersing the modified glass fiber cloth in the resin glue for the copper-clad substrate, taking it out, drying it at 25-30°C, and drying it at 110-120°C for 10-20 minutes to obtain a prepreg;

[0007] The semi-cured sheets are stacked up, and a layer of copper foil is placed on the stacked cured sheets. At 3-5 MPa, the temperature is raised and cured in stages according to (95-105)°C / (0.8-1.2)h, (135-145)°C / (0.8-1.2)h, (155-165)°C / (1.8-2.2)h, (175-185)°C / (1.8-2.2)h, and (195-205)°C / (1.8-2.2)h. After the curing is completed, the sheet is cooled and the burrs are trimmed to obtain a flame-retardant PCB copper-clad substrate.

[0008] As a limitation of the present invention, the preparation method of the resin glue for copper-clad substrate is:

[0009] The fluorine-containing pyridine benzoxazine, epoxy resin, 4,4-diaminodiphenylmethane and acetone are mixed, stirred at 50-70°C and 500-700rpm for 20-30min, KH-550 modified nano-silica hollow spheres and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are added, the temperature is lowered to 20-30°C, and stirring is continued for 0.5-1.5h to obtain a resin glue for copper-clad substrates.

[0010] As a limitation of the present invention, the resin adhesive for the coated board includes, by mass, 23 to 27 parts of fluorine-containing pyridine-type benzoxazine, 63 to 67 parts of epoxy resin, 1 to 3 parts of 4,4-diaminodiphenylmethane, 13 to 15 parts of KH-550 modified nano-silica hollow spheres, 15 to 17 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 145 to 155 parts of acetone.

[0011] As a limitation of the present invention, the preparation method of the fluorinated pyridine-type benzoxazine is:

[0012] Toluene, ethyl acetate and paraformaldehyde are mixed, and stirred at 150-250 rpm for 5-15 min under nitrogen as protective gas to obtain a paraformaldehyde solution. 3,5-difluoro-2,6-diaminopyridine, phenol, toluene and ethyl acetate are mixed and stirred to obtain an aminopyridine / phenol solution. The aminopyridine / phenol solution is slowly added to the paraformaldehyde solution and stirred to obtain an aminopyridine / phenol solution. The mixture is reacted at 80-100° C. and 200-400 rpm under nitrogen as protective gas for 8-12 h. After the reaction is completed, the mixture is allowed to stand and separated into layers. The organic solvent layer is taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated pyridine-type benzoxazine.

[0013] As a limitation of the present invention, the paraformaldehyde solution includes, by mass, 48.70 to 48.74 parts of toluene, 25.24 to 25.28 parts of ethyl acetate, and 7.42 to 7.46 parts of paraformaldehyde.

[0014] As a limitation of the present invention, the aminopyridine / phenol solution includes, by mass, 4.34 to 4.38 parts of 3,5-difluoro-2,6-diaminopyridine, 11.64 to 11.68 parts of phenol, 97.42 to 97.46 parts of toluene, and 50.50 to 50.54 parts of ethyl acetate.

[0015] As a limitation of the present invention, the preparation method of the KH-550 modified nano-silica hollow spheres is:

[0016] The hexadecyltrimethylammonium bromide, ammonia water, ethanol and deionized water are mixed, stirred at 25-30°C and 400-600rpm for 5-15min to obtain a hexadecyltrimethylammonium bromide solution, ethyl orthosilicate is added to the hexadecyltrimethylammonium bromide solution, reacted at 25-30°C and 400-600rpm for 0.5-1.5h, centrifuged after the reaction, washed with deionized water, and dried at 450-550°C for 4-6h to obtain nano hollow silica spheres;

[0017] Mix KH-550, deionized water and ethanol, stir evenly, adjust the pH with acetic acid to obtain KH-550 ethanol solution, mix the nano-silica hollow spheres and the KH-550 ethanol solution, ultrasonically disperse for 10 to 20 minutes, react at 70 to 90° C. for 3 to 5 hours, and obtain KH-550 modified nano-silica hollow spheres.

[0018] As a limitation of the present invention, the preparation of nano-silica hollow spheres includes 0.38-0.42 parts of hexadecyltrimethylammonium bromide, 0.64-0.68 parts of ammonia water, and 0.26-0.30 parts of ethyl orthosilicate, calculated by mass.

[0019] As a limitation of the present invention, the preparation of KH-550 modified nano-silica hollow spheres includes 46 to 50 parts of nano-silica hollow spheres, 1.98 to 2.02 parts of KH-550, 9 to 11 parts of deionized water, and 86 to 90 parts of ethanol, by mass.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] Fluorine-containing pyridine-type benzoxazine prepared from paraformaldehyde, phenol and 3,5-difluoro-2,6-diaminopyridine introduces fluorine atoms to form CF bonds with lower polarity than CH bonds, thereby reducing the polarity of the molecule and increasing the free volume of the molecule, thereby reducing the dielectric constant of the sheet. In addition, the pyridine functional group in the resin not only increases the nitrogen content in the polymer and improves the flame retardancy of the resin matrix, but also increases the intramolecular and intermolecular hydrogen bonds of the resin and enhances the heat resistance of the resin due to the presence of negatively charged nitrogen atoms in the pyridine ring.

[0022] The nano-silica microspheres synthesized with tetraethyl orthosilicate as the silicon source and hexadecyltrimethylammonium bromide as the template have cavities inside. When mixed with resin, they can increase the porosity of the resin material and reduce the number of polarized molecules per unit volume, thereby effectively reducing the dielectric constant of the resin material. In addition, silica itself has the characteristics of high temperature resistance, low thermal expansion coefficient, and stable chemical properties. When mixed with resin, it can also improve the heat resistance and thermal stability of the resin material.

[0023] Silane coupling agents KH-550 and KH-560 were used to modify nano-silica hollow spheres and glass fiber cloth respectively, which improved the compatibility between nano-silica microspheres and glass fiber cloth and the resin, made the materials more tightly combined, and reduced the occurrence of agglomeration of nano-silica microspheres in the resin. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Paraformaldehyde (95%) and epoxy resin (0.48 mol / 100 g) were provided by Shanghai MacLean, and glass fiber cloth (200 g / cm 3 ) provided by Jiangxi Yanhu Fiberglass, copper foil (128g / cm 2 ) provided by Huizhou United Copper Foil.

[0026] Embodiment 1: A method for preparing a flame-retardant PCB copper-clad substrate, specifically:

[0027] Step 1: Preparation of fluorinated pyridine-type benzoxazines

[0028] By mass, 48.72 parts of toluene, 25.26 parts of ethyl acetate and 7.44 parts of paraformaldehyde were mixed, stirred at 200 rpm for 10 min under nitrogen as protective gas to obtain a paraformaldehyde solution, 4.36 parts of 3,5-difluoro-2,6-diaminopyridine, 11.66 parts of phenol, 97.44 parts of toluene and 50.52 parts of ethyl acetate were mixed and stirred uniformly to obtain an aminopyridine / phenol solution, 163.98 parts of the aminopyridine / phenol solution were slowly added to 81.42 parts of the paraformaldehyde solution, stirred uniformly, reacted at 90° C. and 300 rpm under nitrogen as protective gas for 10 hours, and after the reaction was completed, the layers were allowed to stand and separated, the organic solvent layer was taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated pyridine-type benzoxazine.

[0029] Step 2: Preparation of hollow nano-silica spheres

[0030] 0.4 parts of hexadecyltrimethylammonium bromide, 0.66 parts of ammonia water, 36.58 parts of ethanol and 63.42 parts of deionized water were mixed by mass, and stirred at 27°C and 500 rpm for 10 min to obtain a hexadecyltrimethylammonium bromide solution. 0.28 parts of ethyl orthosilicate were added to 101.06 parts of the hexadecyltrimethylammonium bromide solution, and the mixture was reacted at 27°C and 500 rpm for 1 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 500°C for 5 h to obtain nano-silica hollow spheres.

[0031] Step 3: Preparation of KH-550 modified nano-silica hollow spheres

[0032] By mass, 2 parts of KH-550, 10 parts of deionized water and 88 parts of ethanol were mixed and stirred evenly, and the pH was adjusted to 4 with acetic acid to obtain a KH-550 ethanol solution. 48 parts of nano-silica hollow spheres and 100 parts of KH-550 ethanol solution were mixed, ultrasonically dispersed for 15 minutes, and reacted at 80°C for 6 hours to obtain KH-550 modified nano-silica hollow spheres.

[0033] Step 4: Prepare the copper clad substrate resin glue

[0034] By mass, 25 parts of fluorine-containing pyridine benzoxazine, 65 parts of epoxy resin, 2 parts of 4,4-diaminodiphenylmethane, and 150 parts of acetone were mixed, stirred at 60°C and 600rpm for 30min, 14 parts of KH-550 modified nano-silica hollow spheres and 16 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 25°C, and stirring was continued for 1h to obtain a resin glue for copper-clad substrates.

[0035] Step 5: Preparing the prepreg

[0036] Mix 15 parts of KH-560, 50 parts of deionized water and 1.6 parts of methanol, stir evenly, adjust the pH of the solution to 4 with acetic acid, hydrolyze at 27°C for 2 hours to obtain a KH-560 solution, cut the glass fiber cloth into a size of 200mm×200mm, and soak it in the KH-560 solution for 30 minutes to obtain a modified glass fiber cloth, fully immerse the modified glass fiber cloth in the resin glue for the coated board, take it out, dry it at 27°C, and dry it at 115°C for 15 minutes to obtain a semi-cured sheet.

[0037] Step 6: Prepare flame-retardant copper-clad PCB substrate

[0038] Stack 8 semi-cured sheets, and place a layer of copper foil on the stacked cured sheets. At 4 MPa, perform staged temperature curing at 100℃ / 1h, 140℃ / 1h, 160℃ / 2h, 180℃ / 2h, and 200℃ / 2h. After curing, cool and trim the burrs to obtain a flame-retardant PCB copper-clad substrate.

[0039] Embodiment 2: A method for preparing a flame-retardant PCB copper-clad substrate, specifically:

[0040] Step 1: Preparation of fluorinated pyridine-type benzoxazines

[0041] By mass, 48.72 parts of toluene, 25.26 parts of ethyl acetate and 7.44 parts of paraformaldehyde were mixed, stirred at 200 rpm for 10 min under nitrogen as protective gas to obtain a paraformaldehyde solution, 4.36 parts of 3,5-difluoro-2,6-diaminopyridine, 11.66 parts of phenol, 97.44 parts of toluene and 50.52 parts of ethyl acetate were mixed and stirred uniformly to obtain an aminopyridine / phenol solution, 163.98 parts of the aminopyridine / phenol solution were slowly added to 81.42 parts of the paraformaldehyde solution, stirred uniformly, reacted at 90° C. and 300 rpm under nitrogen as protective gas for 10 hours, and after the reaction was completed, the layers were allowed to stand and separated, the organic solvent layer was taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated pyridine-type benzoxazine.

[0042] Step 2: Preparation of hollow nano-silica spheres

[0043] 0.4 parts of hexadecyltrimethylammonium bromide, 0.66 parts of ammonia water, 36.58 parts of ethanol and 63.42 parts of deionized water were mixed by mass, and stirred at 27°C and 500 rpm for 10 min to obtain a hexadecyltrimethylammonium bromide solution. 0.28 parts of ethyl orthosilicate were added to 101.06 parts of the hexadecyltrimethylammonium bromide solution, and the mixture was reacted at 27°C and 500 rpm for 1 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 500°C for 5 h to obtain nano-silica hollow spheres.

[0044] Step 3: Preparation of KH-550 modified nano-silica hollow spheres

[0045] By mass, 2 parts of KH-550, 10 parts of deionized water and 88 parts of ethanol were mixed and stirred evenly, and the pH was adjusted to 4 with acetic acid to obtain a KH-550 ethanol solution. 48 parts of nano-silica hollow spheres and 100 parts of KH-550 ethanol solution were mixed, ultrasonically dispersed for 15 minutes, and reacted at 80°C for 6 hours to obtain KH-550 modified nano-silica hollow spheres.

[0046] Step 4: Prepare the copper clad substrate resin glue

[0047] By mass, 23 parts of fluorine-containing pyridine benzoxazine, 63 parts of epoxy resin, 1 part of 4,4-diaminodiphenylmethane, and 145 parts of acetone were mixed, stirred at 60°C and 600rpm for 30min, 13 parts of KH-550 modified nano-silica hollow spheres and 15 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 25°C, and stirring was continued for 1h to obtain a resin glue for copper-clad substrates.

[0048] Step 5: Preparing the prepreg

[0049] Mix 15 parts of KH-560, 50 parts of deionized water and 1.6 parts of methanol, stir evenly, adjust the pH of the solution to 4 with acetic acid, hydrolyze at 27°C for 2 hours to obtain a KH-560 solution, cut the glass fiber cloth into a size of 200mm×200mm, and soak it in the KH-560 solution for 30 minutes to obtain a modified glass fiber cloth, fully immerse the modified glass fiber cloth in the resin glue for the coated board, take it out, dry it at 27°C, and dry it at 115°C for 15 minutes to obtain a semi-cured sheet.

[0050] Step 6: Prepare flame-retardant copper-clad PCB substrate

[0051] Stack 8 semi-cured sheets, and place a layer of copper foil on the stacked cured sheets. At 4 MPa, perform staged temperature curing at 100℃ / 1h, 140℃ / 1h, 160℃ / 2h, 180℃ / 2h, and 200℃ / 2h. After curing, cool and trim the burrs to obtain a flame-retardant PCB copper-clad substrate.

[0052] Embodiment 3: A method for preparing a flame-retardant PCB copper-clad substrate, specifically:

[0053] Step 1: Preparation of fluorinated pyridine-type benzoxazines

[0054] By mass, 48.72 parts of toluene, 25.26 parts of ethyl acetate and 7.44 parts of paraformaldehyde were mixed, stirred at 200 rpm for 10 min under nitrogen as protective gas to obtain a paraformaldehyde solution, 4.36 parts of 3,5-difluoro-2,6-diaminopyridine, 11.66 parts of phenol, 97.44 parts of toluene and 50.52 parts of ethyl acetate were mixed and stirred uniformly to obtain an aminopyridine / phenol solution, 163.98 parts of the aminopyridine / phenol solution were slowly added to 81.42 parts of the paraformaldehyde solution, stirred uniformly, reacted at 90° C. and 300 rpm under nitrogen as protective gas for 10 h, and after the reaction was completed, the reaction was allowed to stand for stratification, the organic solvent layer was taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorine-containing pyridine-type benzoxazine.

[0055] Step 2: Preparation of hollow nano-silica spheres

[0056] 0.4 parts of hexadecyltrimethylammonium bromide, 0.66 parts of ammonia water, 36.58 parts of ethanol and 63.42 parts of deionized water were mixed by mass, and stirred at 27°C and 500 rpm for 10 min to obtain a hexadecyltrimethylammonium bromide solution. 0.28 parts of ethyl orthosilicate were added to 101.06 parts of the hexadecyltrimethylammonium bromide solution, and the mixture was reacted at 27°C and 500 rpm for 1 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 500°C for 5 h to obtain nano-silica hollow spheres.

[0057] Step 3: Preparation of KH-550 modified nano-silica hollow spheres

[0058] By mass, 2 parts of KH-550, 10 parts of deionized water and 88 parts of ethanol were mixed and stirred evenly, and the pH was adjusted to 4 with acetic acid to obtain a KH-550 ethanol solution. 48 parts of nano-silica hollow spheres and 100 parts of KH-550 ethanol solution were mixed, ultrasonically dispersed for 15 minutes, and reacted at 80°C for 6 hours to obtain KH-550 modified nano-silica hollow spheres.

[0059] Step 4: Prepare the copper clad substrate resin glue

[0060] By mass, 27 parts of fluorine-containing pyridine benzoxazine, 67 parts of epoxy resin, 3 parts of 4,4-diaminodiphenylmethane, and 155 parts of acetone were mixed, stirred at 60°C and 600rpm for 30min, 15 parts of KH-550 modified nano-silica hollow spheres and 17 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 25°C, and stirring was continued for 1h to obtain a resin glue for copper-clad substrates.

[0061] Step 5: Preparing the prepreg

[0062] Mix 15 parts of KH-560, 50 parts of deionized water and 1.6 parts of methanol, stir evenly, adjust the pH of the solution to 4 with acetic acid, hydrolyze at 27°C for 2 hours to obtain a KH-560 solution, cut the glass fiber cloth into a size of 200mm×200mm, and soak it in the KH-560 solution for 30 minutes to obtain a modified glass fiber cloth, fully immerse the modified glass fiber cloth in the resin glue for the coated board, take it out, dry it at 27°C, and dry it at 115°C for 15 minutes to obtain a semi-cured sheet.

[0063] Step 6: Prepare flame-retardant copper-clad PCB substrate

[0064] Stack 8 semi-cured sheets, and place a layer of copper foil on the stacked cured sheets. At 4 MPa, perform staged temperature curing at 100℃ / 1h, 140℃ / 1h, 160℃ / 2h, 180℃ / 2h, and 200℃ / 2h. After curing, cool and trim the burrs to obtain a flame-retardant PCB copper-clad substrate.

[0065] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below:

[0066] Comparative Example 1: The nano-silica hollow spheres were not modified with KH-550, and the other conditions were the same as those in Example 1.

[0067] A method for preparing a flame-retardant PCB copper-clad substrate, specifically comprising:

[0068] Step 1: Preparation of fluorinated pyridine-type benzoxazines

[0069] By mass, 48.72 parts of toluene, 25.26 parts of ethyl acetate and 7.44 parts of paraformaldehyde were mixed, stirred at 200 rpm for 10 min under nitrogen as protective gas to obtain a paraformaldehyde solution, 4.36 parts of 3,5-difluoro-2,6-diaminopyridine, 11.66 parts of phenol, 97.44 parts of toluene and 50.52 parts of ethyl acetate were mixed and stirred uniformly to obtain an aminopyridine / phenol solution, 163.98 parts of the aminopyridine / phenol solution were slowly added to 81.42 parts of the paraformaldehyde solution, stirred uniformly, reacted at 90° C. and 300 rpm under nitrogen as protective gas for 10 hours, and after the reaction was completed, the layers were allowed to stand and separated, the organic solvent layer was taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated pyridine-type benzoxazine.

[0070] Step 2: Preparation of hollow nano-silica spheres

[0071] 0.4 parts of hexadecyltrimethylammonium bromide, 0.66 parts of ammonia water, 36.58 parts of ethanol and 63.42 parts of deionized water were mixed by mass, and stirred at 27°C and 500 rpm for 10 min to obtain a hexadecyltrimethylammonium bromide solution. 0.28 parts of ethyl orthosilicate were added to 101.06 parts of the hexadecyltrimethylammonium bromide solution, and the mixture was reacted at 27°C and 500 rpm for 1 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 500°C for 5 h to obtain nano-silica hollow spheres.

[0072] Step 3: Prepare the copper clad substrate resin glue

[0073] By mass, 25 parts of fluorine-containing pyridine benzoxazine, 65 parts of epoxy resin, 2 parts of 4,4-diaminodiphenylmethane, and 150 parts of acetone were mixed, stirred at 60°C and 600rpm for 30min, 14 parts of nano-silica hollow spheres and 16 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 25°C, and stirring was continued for 1h to obtain a resin glue for copper-clad substrates.

[0074] Step 4: Preparing the prepreg

[0075] Mix 15 parts of KH-560, 50 parts of deionized water and 1.6 parts of methanol, stir evenly, adjust the pH of the solution to 4 with acetic acid, hydrolyze at 27°C for 2 hours to obtain a KH-560 solution, cut the glass fiber cloth into a size of 200mm×200mm, and soak it in the KH-560 solution for 30 minutes to obtain a modified glass fiber cloth, fully immerse the modified glass fiber cloth in the resin glue for the coated board, take it out, dry it at 27°C, and dry it at 115°C for 15 minutes to obtain a semi-cured sheet.

[0076] Step 5: Prepare flame-retardant copper-clad PCB substrate

[0077] Stack 8 semi-cured sheets, and place a layer of copper foil on the stacked cured sheets. At 4 MPa, perform staged temperature curing at 100℃ / 1h, 140℃ / 1h, 160℃ / 2h, 180℃ / 2h, and 200℃ / 2h. After curing, cool and trim the burrs to obtain a flame-retardant PCB copper-clad substrate.

[0078] Comparative Example 2: Nano-silica particles were used instead of nano-silica hollow spheres, and the remaining conditions were the same as those in Example 1.

[0079] A method for preparing a flame-retardant PCB copper-clad substrate, specifically comprising:

[0080] Step 1: Preparation of fluorinated pyridine-type benzoxazines

[0081] By mass, 48.72 parts of toluene, 25.26 parts of ethyl acetate and 7.44 parts of paraformaldehyde were mixed, stirred at 200 rpm for 10 min under nitrogen as protective gas to obtain a paraformaldehyde solution, 4.36 parts of 3,5-difluoro-2,6-diaminopyridine, 11.66 parts of phenol, 97.44 parts of toluene and 50.52 parts of ethyl acetate were mixed and stirred uniformly to obtain an aminopyridine / phenol solution, 163.98 parts of the aminopyridine / phenol solution were slowly added to 81.42 parts of the paraformaldehyde solution, stirred uniformly, reacted at 90° C. and 300 rpm under nitrogen as protective gas for 10 hours, and after the reaction was completed, the layers were allowed to stand and separated, the organic solvent layer was taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated pyridine-type benzoxazine.

[0082] Step 2: Preparation of KH-550 modified nano-silica

[0083] By mass, 2 parts of KH-550, 10 parts of deionized water and 88 parts of ethanol were mixed and stirred evenly, and the pH was adjusted to 4 with acetic acid to obtain a KH-550 ethanol solution. 48 parts of nano-silica and 100 parts of KH-550 ethanol solution were mixed, ultrasonically dispersed for 15 minutes, and reacted at 80°C for 6 hours to obtain KH-550 modified nano-silica.

[0084] Step 3: Prepare the copper clad substrate resin glue

[0085] By mass, 25 parts of fluorine-containing pyridine benzoxazine, 65 parts of epoxy resin, 2 parts of 4,4-diaminodiphenylmethane, and 150 parts of acetone were mixed, stirred at 60°C and 600rpm for 30min, 14 parts of nano-silicon dioxide and 16 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 25°C, and stirring was continued for 1h to obtain a resin glue for copper-clad substrates.

[0086] Step: Preparing a prepreg

[0087] Mix 15 parts of KH-560, 50 parts of deionized water and 1.6 parts of methanol, stir evenly, adjust the pH of the solution to 4 with acetic acid, hydrolyze at 27°C for 2 hours to obtain a KH-560 solution, cut the glass fiber cloth into a size of 200mm×200mm, and soak it in the KH-560 solution for 30 minutes to obtain a modified glass fiber cloth, fully immerse the modified glass fiber cloth in the resin glue for the coated board, take it out, dry it at 27°C, and dry it at 115°C for 15 minutes to obtain a semi-cured sheet.

[0088] Step 5: Prepare flame-retardant copper-clad PCB substrate

[0089] Stack 8 semi-cured sheets, and place a layer of copper foil on the stacked cured sheets. At 4 MPa, perform staged temperature curing at 100℃ / 1h, 140℃ / 1h, 160℃ / 2h, 180℃ / 2h, and 200℃ / 2h. After curing, cool and trim the burrs to obtain a flame-retardant PCB copper-clad substrate.

[0090] Comparative Example 3: Using p-fluoroaniline instead of 3,5-difluoro-2,6-diaminopyridine to prepare fluorinated benzoxazine, the remaining conditions were the same as those in Example 1.

[0091] A method for preparing a flame-retardant PCB copper-clad substrate, specifically comprising:

[0092] Step 1: Preparation of Fluorinated Benzoxazines

[0093] By mass, 48.72 parts of toluene, 25.26 parts of ethyl acetate and 7.44 parts of paraformaldehyde were mixed, and stirred at 200 rpm for 10 min under nitrogen as a protective gas to obtain a paraformaldehyde solution, 4.36 parts of p-fluoroaniline, 11.66 parts of phenol, 97.44 parts of toluene and 50.52 parts of ethyl acetate were mixed and stirred uniformly to obtain a p-fluoroaniline / phenol solution, 163.98 parts of p-fluoroaniline / phenol solution were slowly added to 81.42 parts of the paraformaldehyde solution, stirred uniformly, and reacted at 90°C and 300 rpm for 10 hours under nitrogen as a protective gas. After the reaction was completed, the mixture was allowed to stand for stratification, and the organic solvent layer was taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated benzoxazine.

[0094] Step 2: Preparation of hollow nano-silica spheres

[0095] 0.4 parts of hexadecyltrimethylammonium bromide, 0.66 parts of ammonia water, 36.58 parts of ethanol and 63.42 parts of deionized water were mixed by mass, and stirred at 27°C and 500 rpm for 10 min to obtain a hexadecyltrimethylammonium bromide solution. 0.28 parts of ethyl orthosilicate were added to 101.06 parts of the hexadecyltrimethylammonium bromide solution, and the mixture was reacted at 27°C and 500 rpm for 1 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 500°C for 5 h to obtain nano-silica hollow spheres.

[0096] Step 3: Preparation of KH-550 modified nano-silica hollow spheres

[0097] By mass, 2 parts of KH-550, 10 parts of deionized water and 88 parts of ethanol were mixed and stirred evenly, and the pH was adjusted to 4 with acetic acid to obtain a KH-550 ethanol solution. 48 parts of nano-silica hollow spheres and 100 parts of KH-550 ethanol solution were mixed, ultrasonically dispersed for 15 minutes, and reacted at 80°C for 6 hours to obtain KH-550 modified nano-silica hollow spheres.

[0098] Step 4: Prepare the copper clad substrate resin glue

[0099] By mass, 25 parts of fluorinated benzoxazine, 65 parts of epoxy resin, 2 parts of 4,4-diaminodiphenylmethane, and 150 parts of acetone were mixed, stirred at 60°C and 600rpm for 30min, 14 parts of KH-550 modified nano-silica hollow spheres and 16 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 25°C, and stirring was continued for 1h to obtain a resin glue for copper-clad substrates.

[0100] Step 5: Preparing the prepreg

[0101] Mix 15 parts of KH-560, 50 parts of deionized water and 1.6 parts of methanol, stir evenly, adjust the pH of the solution to 4 with acetic acid, hydrolyze at 27°C for 2 hours to obtain a KH-560 solution, cut the glass fiber cloth into a size of 200mm×200mm, and soak it in the KH-560 solution for 30 minutes to obtain a modified glass fiber cloth, fully immerse the modified glass fiber cloth in the resin glue for the coated board, take it out, dry it at 27°C, and dry it at 115°C for 15 minutes to obtain a semi-cured sheet.

[0102] Step 6: Prepare flame-retardant copper-clad PCB substrate

[0103] Stack 8 semi-cured sheets, and place a layer of copper foil on the stacked cured sheets. At 4 MPa, perform staged temperature curing at 100℃ / 1h, 140℃ / 1h, 160℃ / 2h, 180℃ / 2h, and 200℃ / 2h. After curing, cool and trim the burrs to obtain a flame-retardant PCB copper-clad substrate.

[0104] Detection experiment:

[0105] The flame-retardant PCB copper-clad substrate required for the test was prepared according to the preparation methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.

[0106] Heat resistance test: Dynamic mechanical analysis (DMA) was used to test each sample with a sample size of 5 mm × 5 mm × 1 mm to measure the glass transition temperature Tg of the resin material.

[0107] Flame retardant performance test: According to the UL94V0 vertical combustion standard, the CZF-2 comprehensive vertical combustion tester is used for measurement. Take 5 samples of 125mm×13mm×3mm respectively, adjust the flame height of the vertical combustion instrument to about 2cm, ignite one end of the sample vertically on the flame for 1 second, remove the flame, and record the time from the sample to self-extinguishing. Each sample is ignited twice, and the afterburning time after 10 ignitions is recorded. The maximum afterburning time does not exceed 10 seconds, the average afterburning time of 10 times does not exceed 5 seconds, and there is no phenomenon of dripping igniting cotton balls, which is UL94 V-0 level; the maximum burning time does not exceed 30 seconds, the average burning time does not exceed 25 seconds, and there is no phenomenon of dripping igniting cotton balls, which is UL94 V-1 level; the maximum burning time does not exceed 30 seconds, the average burning time does not exceed 25 seconds, and there is a phenomenon of dripping igniting cotton balls, which is UL94 V-2 level.

[0108] Dielectric performance test: Based on the flat plate capacitance method, the TZDM-RT-300 dielectric measuring instrument is used to put a sample with a diameter of 50 mm into the resonant circuit of the measuring instrument. The frequency is 1 to 100 MHz, and the dielectric constant and dielectric loss of the sample are tested.

[0109]

[0110] Conclusion: It can be seen from the experiment that the heat resistance, solder immersion resistance, flame retardancy and dielectric properties of the flame retardant PCB copper clad substrate prepared by the preparation method of Example 1 are better than those of the flame retardant PCB copper clad substrate prepared by the preparation methods of Comparative Examples 1, 2 and 3, which effectively solves the problems of insufficient heat resistance and flame retardancy of the PCB copper clad substrate. The dielectric constant and dielectric loss of the sample of Example 1 are lower than those of the samples of Comparative Examples 1, 2 and 3, which is conducive to the development of high-frequency, high-speed, high-performance PCB boards.

[0111] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a flame-retardant PCB copper-clad substrate, characterized in that: The preparation method is: After cutting the glass fiber cloth into a suitable size, modifying it with KH-560, fully immersing the modified glass fiber cloth in the resin glue for the copper-clad substrate, taking it out, drying it at 25-30°C, and drying it at 110-120°C for 10-20 minutes to obtain a prepreg; The semi-cured sheets are stacked up, and a layer of copper foil is placed on the stacked cured sheets. At 3-5 MPa, the temperature is raised and cured in stages according to (95-105)°C / (0.8-1.2)h, (135-145)°C / (0.8-1.2)h, (155-165)°C / (1.8-2.2)h, (175-185)°C / (1.8-2.2)h, and (195-205)°C / (1.8-2.2)h. After the curing is completed, the sheet is cooled and the burrs are trimmed to obtain a flame-retardant PCB copper-clad substrate.

2. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 1, characterized in that: The preparation method of the resin glue for copper-clad substrate is as follows: The fluorinated pyridine-type benzoxazine, epoxy resin, 4,4-diaminodiphenylmethane and acetone were mixed, stirred at 50-70° C. and 500-700 rpm for 20-30 min, KH-550 modified nano-silica hollow spheres and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added, the temperature was lowered to 20-30° C., and stirring was continued for 0.5-1.5 h to obtain a resin adhesive for a copper-clad substrate.

3. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 2, characterized in that: Calculated by mass, the resin adhesive for the coated board includes 23 to 27 parts of fluorine-containing pyridine-type benzoxazine, 63 to 67 parts of epoxy resin, 1 to 3 parts of 4,4-diaminodiphenylmethane, 13 to 15 parts of KH-550 modified nano-silica hollow spheres, 15 to 17 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 145 to 155 parts of acetone.

4. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 2, characterized in that: The preparation method of fluorinated pyridine-type benzoxazine is as follows: Toluene, ethyl acetate and paraformaldehyde are mixed, and stirred at 150-250 rpm for 5-15 min under nitrogen as protective gas to obtain a paraformaldehyde solution. 3,5-difluoro-2,6-diaminopyridine, phenol, toluene and ethyl acetate are mixed and stirred to obtain an aminopyridine / phenol solution. The aminopyridine / phenol solution is slowly added to the paraformaldehyde solution and stirred to obtain an aminopyridine / phenol solution. The mixture is reacted at 80-100° C. and 200-400 rpm under nitrogen as protective gas for 8-12 h. After the reaction is completed, the mixture is allowed to stand and separated into layers. The organic solvent layer is taken, rotary evaporated, and vacuum dried to remove the solvent to obtain a fluorinated pyridine-type benzoxazine.

5. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 4, characterized in that: The paraformaldehyde solution includes 48.70-48.74 parts of toluene, 25.24-25.28 parts of ethyl acetate, and 7.42-7.46 parts of paraformaldehyde in parts by mass.

6. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 4, characterized in that: In parts by mass, the aminopyridine / phenol solution includes 4.34 to 4.38 parts of 3,5-difluoro-2,6-diaminopyridine, 11.64 to 11.68 parts of phenol, 97.42 to 97.46 parts of toluene, and 50.50 to 50.54 parts of ethyl acetate.

7. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 2, characterized in that: The preparation method of KH-550 modified nano-silica hollow spheres is as follows: The hexadecyltrimethylammonium bromide, ammonia water, ethanol and deionized water are mixed, stirred at 25-30°C and 400-600rpm for 5-15min to obtain a hexadecyltrimethylammonium bromide solution, ethyl orthosilicate is added to the hexadecyltrimethylammonium bromide solution, reacted at 25-30°C and 400-600rpm for 0.5-1.5h, centrifuged after the reaction, washed with deionized water, and dried at 450-550°C for 4-6h to obtain nano hollow silica spheres; Mix KH-550, deionized water and ethanol, stir evenly, adjust the pH with acetic acid to obtain KH-550 ethanol solution, mix the nano-silica hollow spheres and the KH-550 ethanol solution, ultrasonically disperse for 10 to 20 minutes, react at 70 to 90° C. for 3 to 5 hours, and obtain KH-550 modified nano-silica hollow spheres.

8. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 7, characterized in that: The preparation of nano hollow silicon dioxide spheres includes 0.38-0.42 parts of hexadecyltrimethylammonium bromide, 0.64-0.68 parts of ammonia water, and 0.26-0.30 parts of ethyl orthosilicate, based on mass.

9. The method for preparing a flame-retardant PCB copper-clad substrate according to claim 7, characterized in that: The preparation method of KH-550 modified nano-silica hollow spheres includes 46-50 parts of nano-silica hollow spheres, 1.98-2.02 parts of KH-550, 9-11 parts of deionized water, and 86-90 parts of ethanol, based on mass.

Citation Information

Patent Citations

  • Flame-retarded resin glue solution used for copper-clad plate and preparation method of flame-retarded resin glue solution

    CN107759978A

  • Voltage-resistant and high-temperature-resistant high-frequency copper-clad substrate and preparation method thereof

    CN113829700A

  • Preparation method of copper-clad plate with low dielectric constant, low dielectric loss and low CTE

    CN113978061A

  • High-frequency and high-speed PPO resin-based copper-clad plate and preparation process thereof

    CN116512702A

  • Halogen-free resin composition and prepreg and laminated board prepared therefrom

    WO2016074290A1